Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1365-2710.2008.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various estimates of renal function on prediction of vancomycin concentration by the population mean and Bayesian methods

Abstract: In the application of the PM method for VCM treatment of elderly patients with MRSA, substitution of SCR based on the Jaffe method into the Cockcroft-Gault equation increases the predictability of the serum VCM trough level. The Bayesian method predicted the serum VCM trough level with high accuracy using any of the estimates of renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The coefficients of the CG equation have never been revised for modern, IDMS traceable serum creatinine assays. Tsuji et al have shown that converting enzymatic S Cr values into corresponding Jaffe values may significantly improve the performance of the CG equation as a covariate to predict vancomycin concentrations (34). However, in our opinion, it is unlikely that clinicians will perform such conversion in routine clinical practice.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The coefficients of the CG equation have never been revised for modern, IDMS traceable serum creatinine assays. Tsuji et al have shown that converting enzymatic S Cr values into corresponding Jaffe values may significantly improve the performance of the CG equation as a covariate to predict vancomycin concentrations (34). However, in our opinion, it is unlikely that clinicians will perform such conversion in routine clinical practice.…”
Section: Discussionmentioning
confidence: 86%
“…A study conducted with Japanese elderly patients compared the performance of the CG equation based on enzymatic S Cr , the CG equation based on Jaffeconverted S Cr , and the MDRD equation in predicting vancomycin trough levels using a Bayesian approach (34). When the mean value of the population PK parameters was used to predict vancomycin concentrations (a priori prediction), the CG equation based on Jaffe-converted S Cr provided the best predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the optimized CG equation was the most appropriate of the three equations examined to dose renally eliminated drugs. Conversely, a study by Tsuji et al found that if the serum creatinine is measured using the Jaffe method, instead of the IDMS method, then a correction of serum creatinine to 0.68 mg/dL is unnecessary within the CG equation [56]. Additionally, a study by Glatard et al found that the CG equation, MDRD equation, and CKD-EPI equations are not interchangeable when calculating vancomycin dosing and prediction of concentrations based on renal function [57].…”
Section: Key Clinical Issuesmentioning
confidence: 99%
“…As vancomycin is approximately 90% renally eliminated unchanged in the urine [56, 57], it is imperative to accurately estimate renal function when calculating dosing regimens to help optimize the pharmacokinetic and pharmacodynamic properties of the drug. Cutler et al compared vancomycin kinetics in younger patients (mean age: 23 years) versus older patients (mean age: 68 years) [58].…”
Section: Key Clinical Issuesmentioning
confidence: 99%
“…Furthermore, the predictability of the serum concentration of VCM based on TDM estimated by the Cockcroft-Gault equation has been reported to be high in the elderly. 21) Thus, in this study, CrCL calculated with the Cockcroft-Gault equation was used as a substitute for the level of renal function.…”
Section: Discussionmentioning
confidence: 99%